Insect Behavior and Physiological Adaptation Mechanisms Under Starvation Stress - Zhang, Dao-Wei; Xiao, Zhong-Jiu; Zeng, Bo-Ping; Li, Kun; Tang, Yan-Long (Frontiers in Physiology, 2019)
Intermittent food shortages are commonly encountered in the wild. During winter or starvation stress, mammals often choose to hibernate while insects—in the form of eggs, mature larvae, pupae, or adults opt to enter diapause. In response to food shortages, insects may try to find sufficient food to maintain normal growth and metabolism through distribution of populations or even migration. In the face of hunger or starvation, insect responses can include changes in behavior and/or maintenance of a low metabolic rate through physiological adaptations or regulation. For instance, in order to maintain homeostasis of the blood sugar, trehalose under starvation stress, other sugars can be transformed to sustain basic energy metabolism. Furthermore, as the severity of starvation increases, lipids (especially triglycerides) are broken down to improve hunger resistance. Starvation stress simultaneously initiates a series of neural signals and hormone regulation processes in insects. These processes involve neurons or neuropeptides, immunity-related genes, levels of autophagy, heat shock proteins and juvenile hormone levels which maintain lower levels of physiological metabolic activity. This work focuses on hunger stress in insects and reviews its effects on behavior, energy reserve utilization, and physiological regulation. In summary, we highlight the diversity in adaptive strategies of insects to hunger stress and provides potential ideas to improve hunger resistance and cold storage development of natural enemy insects. This gist of literature on insects also broadens our understanding of the factors that dictate phenotypic plasticity in adjusting development and life histories around nutritionally optimal environmental conditions.